EFIKASI MANAJERIAL PEMIMPIN DALAM MENGEMBANGKAN LEMBAGA BARU DI MUHAMMADIYAH BOARDING SCHOOL KARANG RINGIN II MUBA - Ade Sentia Arsy Sabila; Kasinyo Harto; Fitri Ovie Yanti; Amjad, Haidarul (Irfani, 2025)
ABSTRACT This article examines "Managerial Efficacy of Leaders in Developing New Institutions in Muhammadiyah Boarding School Karang Ringin II Muba" with the aim of understanding the role of managerial efficacy of leaders in the development of new educational institutions in the midst of contemporary educational challenges. Using a qualitative approach with the type of case study, data were collected through in-depth interviews, observations, and document analysis. The results show that leaders with high managerial effectiveness are able to manage their own potential and resources, improve teacher skills, adapt to changes in the environment, and implement flexible and adaptive leadership strategies. The implications of these findings underscore the importance of developing the capacity of leaders in the management of educational institutions and implementing innovative strategies to overcome existing challenges. The proposed suggestions include the need for ongoing training and professional development programs for leaders and teachers to improve the efficacy and quality of education in institutions. This research is expected to provide valuable insights for stakeholders in the world of education to create a quality and sustainable institution. Keywords: Managerial Efficacy, Education, Leadership, Boarding School